Yu Xiusong’s personnel files as a historical source in the study of communist movement in China - Natalia L. Mamaeva (RUDN Journal of World History)
One of the directions in Chinese historiography is a research into life and work of outstanding Chinese political figures that might gradually cover “the blank spots” in the history of China. In the spirit of the times, Russian researchers are increasingly turning to the study of archival materials that shed light on the activism of prominent Chinese political activists. Yu Xiusong’s Personnel Files, kept in the collections of Russian State Archive of Socio-Political History, is one of the principal sources on his life and activities. The study looks at Yu Xiusong’s involvement in historical events in China - the CPC foundation, the CPC-Kuomintang United Front, etc. - and refines some well-ingrained views on the history of CPC and national revolutionary movement in China. The study also analyses the problem of initial cooperation between the CPC and the Kuomintang, known as the United Front of Progressive Forces based on cooperation between the CPC and the Kuomintang (1922-1927).